2016
DOI: 10.1037/fam0000209
|View full text |Cite
|
Sign up to set email alerts
|

Parental problem drinking and children’s sleep: The role of ethnicity and socioeconomic status.

Abstract: We examined relations between mothers’ and fathers’ problem drinking and school-aged children’s sleep. Consistent with a health disparities perspective, children’s ethnicity and socioeconomic status were examined as moderators of relations between parental problem drinking and children’s sleep. Participants were 282 children (M age = 9.44 years) and their parents. Children were from diverse ethnic (65% European American, 35% African American) and socioeconomic backgrounds. Using a multi-informant design, paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 72 publications
(111 reference statements)
3
21
4
Order By: Relevance
“…Family risk including interpartner aggression (Kelly & El‐Sheikh, ), parenting stress, reduced social support among parents, and less marital satisfaction (Bernier et al., ) compromise sleep to a greater degree for children from lower SES backgrounds. The longitudinal analyses build on these studies and on a previous investigation that demonstrated cross‐sectional relations between fathers’ PD and children's sleep problems to be more robust for lower SES children (Kelly & El‐Sheikh, ). For children from lower but not higher SES backgrounds, fathers’ PD predicted shortening of sleep duration and worsening of sleep quality including sleep efficiency, long wake episodes, and sleep latency 1 year later.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Family risk including interpartner aggression (Kelly & El‐Sheikh, ), parenting stress, reduced social support among parents, and less marital satisfaction (Bernier et al., ) compromise sleep to a greater degree for children from lower SES backgrounds. The longitudinal analyses build on these studies and on a previous investigation that demonstrated cross‐sectional relations between fathers’ PD and children's sleep problems to be more robust for lower SES children (Kelly & El‐Sheikh, ). For children from lower but not higher SES backgrounds, fathers’ PD predicted shortening of sleep duration and worsening of sleep quality including sleep efficiency, long wake episodes, and sleep latency 1 year later.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study found that children of parents who had a dependency on alcohol had shorter self‐reported and actigraphy‐derived sleep duration (Hairston et al., ). In a recent investigation that used a community sample, PPD was associated cross‐sectionally with shorter actigraphy‐derived sleep duration and worse sleep quality, particularly for African American children and those from lower income homes (Kelly & El‐Sheikh, ). In that study, fathers’ PD was more influential than mothers’ PD for children's sleep (Kelly & El‐Sheikh, ).…”
Section: This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Fifth, sleep and family functioning are associated in complex ways, and some of the most informative investigations are those that incorporate additional levels of influence, such as the broader sociocultural context (11, 45) or individual differences in children’s physiological regulation (42). For example, the importance of assessing many levels of influence is illustrated by the finding that mothers’ depressive symptoms interacted with children’s vagal regulation (an index of parasympathetic nervous system activity) to predict sleep problems longitudinally (42): Children most at risk for poor sleep were those with both depressed mothers and less optimal vagal regulation.…”
Section: Moving Forwardmentioning
confidence: 99%